Inverted Mirrors: The Spanish Weekly Cambio 16 and the Argentine Dictatorship (1976-1978) - Iturralde, Micaela (Revista de Historia Social y de las Mentalidades, 2026)
This article analyzes the journalistic coverage of the repressive regime established by the Argentine military dictatorship following the March 1976 coup d’état in the Spanish weekly Cambio 16. Within the context of Spain’s democratic transition, this widely circulated and influential political magazine became one of the most important print media outlets of the period, distinguished by its sustained attention to the dictatorships of the Southern Cone. Operating outside the information restrictions in place in Argentina and in conjunction with networks of exiled journalists, Cambio 16 developed a systematic and rigorous approach that denounced state violence, forced disappearances, forms of censorship and information control, as well as the propaganda campaigns waged by the regime abroad. Its coverage combined political analysis, documentation, testimonies, and photojournalism, giving central importance to the critical situation of the press and the persecution of journalists. At the same time, the magazine used the Argentine case as a framework for comparative reflection: the repression and authoritarianism observed in the Southern Cone served as a mirror from which to contribute to addressing some of the central themes of the Spanish transition to democracy.